Posted by **luna** on Tuesday, November 22, 2011 at 2:59pm.

solve the equation

1). (x+4)(x-12)=5x

2). 4x^2+2x-14=16-17x

- college math -
**Steve**, Tuesday, November 22, 2011 at 11:24pm
This is an example of why we always get everything on the left side, then factor to make the product zero:

(x+4)(x-12) = 5x

x^2 - 8x - 48 = 5x

x^2 - 13x - 48 = 0

(x-16)(x+3) = 0

Now we have a zero product. That means that if any of the factors is zero, then the product is also zero.

So, x = -3 or 16

Now do the same steps with the second equation

## Answer This Question

## Related Questions

- Math help Steve? - 1) Given that p(-3), p(-1), and p(5)=0, which expression ...
- Math - solve the equation 20x^3 +44x^2 -17x -5 given that -5/2 is a zero of f(x...
- Algebra - Solve: 5x-3=11+12x; 17x-3=11; 17x-3+3=11+3= 17x=14; x= 14/17 is this ...
- Math - 1) Given that p(-3), p(-1), and p(5)=0, which expression could be p(x)? A...
- Math - 1) Given that p(-3), p(-1), and p(5)=0, which expression could be p(x)? A...
- help in math - solve and check each of the following quadratic equation (1) x^2=...
- college algebra - how do I solve this: (17x^3-5x^2+4x-3)-(5x^3-9x^2-8x+11) and ...
- Algebra 1 - solve each equation x(x - 3) - x(x+4)=17x - 23
- algebra - If (x-3) is a factor of 3x^3+bx^2-17x-12. a. Find the value of b. b....
- math - Solve the following equation. (Examples 1-6) 15x2 = -17x + 4 x = 1 (...

More Related Questions